A Harris-Todaro agent-based model to rural-urban migration - Espíndola, Aquino L.; Silveira, Jaylson J. [UNESP]; Penna, T. J P (FapUNIFESP (SciELO), 2006)
The Harris-Todaro model of the rural-urban migration process is revisited under an agent-based approach. The migration of the workers is interpreted as a process of social learning by imitation, formalized by a computational model. By simulating this model, we observe a transitional dynamics with continuous growth of the urban fraction of overall population toward an equilibrium. Such an equilibrium is characterized by stabilization of rural-urban expected wages differential (generalized Harris-Todaro equilibrium condition), urban concentration and urban unemployment. These classic results obtained originally by Harris and Todaro are emergent properties of our model.
Keywords: Agent-based model; Complex system; Econophysics; Harris-Todaro model